(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Among musculoskeletal disorders, low back pain (LBP) has the highest prevalence worldwide and is the primary cause of disability. This is the condition that has the highest potential for rehabilitation benefits Chronic LBP is a major cause of work loss and participation restriction and reduced quality of life around the world. In Ayurveda low back pain is correlated with Kateegraha. Shringa avcharana is one of the methods of Raktamokshana and this can be correlated with Chinese cupping method. The suction through specific cupped instrument was used since prehistoric time for the treatment of disease Objective: This case series aims to show how wet cupping affects lower back pain (Kateegraha). Intervention: five patients who complained of low back pain were included to receive four sittings of wet cupping. Cups were applied on the lumbosacral region once every 7 days for 21 days. The visual analogue scale (VAS) and The Quebec Back Pain Disability Scale was used to evaluate the pain on 7 days, 14 days, and 21 days. Conclusion: It’s been demonstrated that wet cupping works well for relieving Kateegraha (low back pain). So, we can conclude that for individuals with low back pain, wet cupping is a successful, safe, practical, and reasonably priced treatment plan.